Compulsory Psychiatric Admissions in an Italian Urban Setting: Are They Actually Compliant to the Need for Treatment Criteria or Arranged for Dangerous Not Clinical Condition? - Oliva, Francesco; Ostacoli, Luca; Versino, Elisabetta; Portigliatti Pomeri, Alberto; Furlan, Pier Maria; Carletto, Sara; Picci, Rocco Luigi (Frontiers in Psychiatry, 2019)
Background: Italy was one of the first European countries adopting the need for treatment criteria for compulsory admission (CA). The aim of the present study was to confirm whether CA in an urban setting in Italy was compliant with the requested clinical criteria. Methods: In this retrospective observational study, we retrieved all collected information regarding CA in Turin (Italy) from January 2006 to December 2013. All content and data reported in the CA forms, including diagnosis and clinical details, were gathered and analyzed. Comparisons between CA with and without a diagnosis of DSM-IV psychiatric disorders and between different diagnoses were performed using either parametric or non-parametric tests, depending on variable distribution. Results: Three hundred and two (10.5%) of 2870 consecutive CAs made in Turin during a lag time of eight years were due to unknown psychiatric diagnoses (113; 3.9%) or to psychomotor agitation (189; 6.6%). The most prevalent psychiatric disorders leading to CA were schizophrenia (729; 25.4%), brief psychotic disorder (627; 21.8%), bipolar disorder episode (396; 13.8%), delusional disorder (292; 10.2%), and personality disorder (237; 8.3%). The CAs due to psychiatric disorder were longer (U = 328875.0; p < 0.001) and involved patients who were more likely to be compulsorily admitted during the study period (U = 357012.5; p = 0.003), to have had prior contact with a psychiatrist (χ2(2) = 28.34; p < 0.001), to have had previous admissions to a psychiatric ward (χ2(2) = 33.06; p < 0.001), to be under the care of psychiatric services (χ2(3) = 87.01; p < 0.001), and not to have concurrent alcohol (χ2(1) = 23.06; p < 0.001) and/or drug use (χ2(1) = 12.97; p < 0.001) than those due to psychomotor agitation/unspecified diagnoses. Conclusion: Despite a history of 35 years of CA made according to a strict need for treatment criteria, the evaluation of CA records show that a certain proportion of CAs appear to have been due to brief, not psychiatric, alcohol/drug related behavioral conditions. Further studies should confirm the need for law reform leading to the integration between the need for treatment and the danger criteria for CAs.